Make-or-Buy Decisions in Patent Related Services - Stefan Wagner (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2006)
Among the most prominent theoretical frameworks dealing with the economic underlyings of firms' make-or-buy decisions are Transaction Cost Economics (TCE) and the Resourced Based View (RBV). Relying on panel data covering 107 European firms over eight years I test predictions from both TCE and RBV with regard to the outsourcing of patent related services simultaneously. Modelling the share of outsourced patent applications in a Negative Binomial Panel Regression Model I find joint explanatory power of both approaches. My findings support previous literature arguing for an integration of TCE and RBV to a comprehensive theoretical framework of firms make-or-buy decisions.
urn:nbn:de:bvb:19-epub-1264-1
Keywords: L24; L22; 650; outsourcing; patent attorney; make-or-buy; negative binomial panel regression